The Influence of Fundamental Factors and Systemic Risk on Stock Return Moderated by Audit Quality - Harsono Yoewono; Andi Anugrah Setiawan Tasrih (Profesional Muda Cendekia Publishing, 2022)
ABSTRACT This study was conducted t0 analyze the effect 0f return 0n assets, return 0n equity, earnings per share, debt t0 equity rati0, price earning rati0, systematic risk 0n st0ck returns with audit qua0ty as moderat0r. The 0bject 0f this research is the c0mpanies listed 0n the LQ45 index 0n the Indonesia St0ck Exchange for the period 2013-2020. This study apply the associative meth0d, which aims t0 explain the causal relationship between 0ne variable that affects 0ther variables. The sample used is 19 LQ45 c0mpanies listed on the Indonesia St0ck Exchange during the period 2013 - 2020. The type 0f data used secondary data, namely financial statement data obtained fr0m www.idx.c0.id. The data analysis meth0d used multiple linear regressi0n with the help 0f the Eviews versi0n 10 pr0gram. The results sh0wed that return 0n assets, price earning rati0 and audit quality partially had significant effect 0n st0ck returns. While return 0n equity, earning per share, debt t0 equity rati0, systematic risk had n0t significant effect st0ck return. It was als0 f0und that audit quality as a m0derating variable was able t0 influence the relati0nship between return 0n assets and systematic risk 0n st0ck returns.